(3CNHGQ ecI TQagG Gddg heG LGA ajgG ef GdBKGQs - (3GdGRQbj , eMeO Hf YHO Gddg Hf CMeO Hf eMeO Hf GdhdjO Hf YbHg Hf GdCRQb, CHh GdhdjO,J (B250 (3g` s
(3ChdgG (B:s
(3CNHQfi hGdPi Gdabjg GdejGfTi Yf CdCRQbi QVi Gddg Yfg PcQ eG cGfJ GdcYHI Ydjg ahb GdeGA bHd Cf jNdb Gddg GdSehGJ hGdCQV s
(3BNQgG (B:s
(3jfJgi CKfGA HGH (B" (3PcQ eYdGI ecI GdjeGfi heG ajg eeG jYQa GSeg ef GdehGVY hGdLHGd hBNQ eG ajg (B: (3hCHh jRjO cGdYLhR GdeDJeI hVQHhg HGdSjha GdeSdeI s
(3cJHJ HNW bdjd GdEYLGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B198s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs